Function-first ligandomics for ocular vascular research and drug target discovery. (May 2019) - Rong, Xin; Tian, Hong; Yang, Liu; Li, Wei
Abstract: Human eyes may develop different vascular diseases with neovascularization and/or leakage, including wet age-related macular degeneration (AMD), diabetic macular edema (DME), proliferative diabetic retinopathy (PDR), retinopathy of prematurity, corneal neovascularization and intraocular tumors. A breakthrough in therapy is the advent and approval of vascular endothelial growth factor (VEGF) inhibitors. However, anti-VEGF drugs not only have limited efficacy to treat AMD, DME and PDR but also are not approved for other ocular indications. The key to addressing these unmet clinical needs is to develop novel therapies against VEGF-independent angiogenic factors or signaling pathways for alternative or combination therapy. We recently developed the first paradigm of ligandomics for global mapping of cell-wide ligands as well as disease-selective ligands. Therapies targeting disease-selective angiogenic or vascular leakage factors likely have high efficacy, minimal side effects, wide therapeutic windows and relatively low drug attrition rates. A critical challenge is how to distinguish between genuine drug targets and spurious hits identified by high-throughput ligandomics. Here we exploited the unique advantages of the eye and extracellular ligands by combining ligandomics with "function-first" and/or "therapy-first" analyses to efficiently characterize functional activity, disease selectivity, pathogenic role and therapeutic potential of identified ligands. The innovative function- or therapy-first ligandomics will systematically and reliably delineate disease-selective angiogenic or vascular leakage factors and markedly facilitate ocular vascular research and ligand-guided targeted anti-angiogenic therapy. Graphical abstract: Image 1 Highlights: A new concept of function- and/or therapy-first comparative ligandomics. Ligandomics is the only technology to globally map cell-wide ligands. The only high-throughput approach to map disease-selective cellular ligands. Efficient and reliable identification and validation of disease-selective ligands. Disease-selective ligands are high-quality drug targets with minimal side effects.